2006
DOI: 10.1161/01.res.0000205766.97556.00
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Can Prevent and Reverse the Severity of Hypertrophic Cardiomyopathy

Abstract: Abstract-Hypertrophic cardiomyopathy (HCM) is the most common form of sudden death in young competitive athletes.However, exercise has also been shown to be beneficial in the setting of other cardiac diseases. We examined the ability of voluntary exercise to prevent or reverse the phenotypes of a murine model of HCM harboring a mutant myosin heavy chain (MyHC). No differences in voluntary cage wheel performance between nontransgenic (NTG) and HCM male mice were seen. Exercise prevented fibrosis, myocyte disarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
125
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(148 citation statements)
references
References 34 publications
16
125
2
3
Order By: Relevance
“…21 Although swimming significantly increased HW/BW in both groups, expression of GSK-3␤-DN failed to exert an additive effect on the swimming-induced hypertrophy observed in NTg (supplemental Figure VIII). Together with recent evidence that GSK-3␤ is phosphorylated in response to exercise, 22 these results suggest that GSK-3␤-DN-and exercise-induced (physiological) hypertrophy are mediated in part through a common signaling mechanism.…”
Section: Inhibition Of Gsk-3␤ Failed To Exert An Additive Effect On Esupporting
confidence: 65%
See 1 more Smart Citation
“…21 Although swimming significantly increased HW/BW in both groups, expression of GSK-3␤-DN failed to exert an additive effect on the swimming-induced hypertrophy observed in NTg (supplemental Figure VIII). Together with recent evidence that GSK-3␤ is phosphorylated in response to exercise, 22 these results suggest that GSK-3␤-DN-and exercise-induced (physiological) hypertrophy are mediated in part through a common signaling mechanism.…”
Section: Inhibition Of Gsk-3␤ Failed To Exert An Additive Effect On Esupporting
confidence: 65%
“…These observations are relevant to the mechanism of heart failure because physiological hypertrophy could negatively regulate the development of pathological hypertrophy. 22 GSK-3␤ phosphorylates GATA4 and eIF2B, thereby inhibiting cardiac hypertrophy through inhibition of either gene expression or protein translation. 4,6 Because GATA4 protects the heart from load-induced heart failure, 27 the Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, exercise training promoted the same beneficial effects as induced by sustained treatment with cyclosporine (a selective inhibitor of the calcineurin/NFAT pathway) in HF (20). In agreement with our findings, Konhilas et al (49) demonstrated that voluntary exercise decreased NFAT activation and reversed cardiac disease phenotypes in an animal model of hypertrophic cardiomyopathy. These findings clearly demonstrate that deactivation of the calcineurin/NFAT signaling pathway is a key process involved in the exercise training-induced cardiac anti-remodeling effect in HF.…”
Section: Impact Of Exercise Training On Cardiac Remodelingsupporting
confidence: 91%
“…There are no data to support a detrimental effect of exercise in patients with HCM and no evidence that long‐term athletic training may promote an exacerbation of the underlying disease process. In animal models, routine exercise before the development of cardiac phenotype prevented subsequent fibrosis, myocyte disarray, and induction of markers of hypertrophy in mutant myosin heavy chain mice 46. Conversely, in non‐mutant rats conditioned to run vigorously for up to 16 weeks, cardiac fibrosis, changes in ventricular function, and increased arrhythmic propensity were observed 47.…”
Section: Habits and Lifestylementioning
confidence: 99%